Implementasi Hukum PT. Garuda Indonesia Terhadap Kerugian Kehilangan Atau Kerusakan Barang Bagasi Konsumen Di Bandara Djalaludin - Anggriani Ibrahim; Nirwan Junus; Sri Nanang Meiske Kamba (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
The purpose of this research is to find out how PT Garuda Indonesia is responsible for loss or damage to consumer baggage at Djalaludin airport and to find out the form and legal consequences of loss or damage to Garuda Indonesia airline baggage at Djalaludin Djalaludin Airport, Gorontalo Province. This research uses the type of research used is a sociological juridical approach. The data sources used consist of primary and secondary. The results of this research show that the responsibility of the Garuda airline can be seen from the implementation of the airline's responsibility to consumers, however in this research there is still a lack of responsibility by the airline. The airline should be more careful in checking consumer goods so that there are no problems with loss or damage to goods and the airline can fulfill its obligations to provide compensation to compensate for losses experienced by passengers, but in this case the airline is still not giving enough responsibility to passengers. . The factors causing damage and loss of baggage are lack of supervision in the transportation process and passengers not paying attention to advice from the airport and the airline.